(untitled) (Bangladesh Journal of Medical Science, 2022)
Background:Epidural hematoma (EDH) is accumulation of blood between the inner table of the skull and thedural membrane due to trauma and predominantly consists of venous blood in case ofchildren.Children with extradural hematoma (EDH) present differently than adults and outcome would also be different. Methods and Materials: This is a prospective interventional study done in the Department of Neurosurgery, Dhaka Medical College and Hospital (DMCH) in between period of January 2016 to December 2019. Children of both sex below 12 years of age with EDH were included after fulfilling inclusion and exclusion criteria. Follow up period was 1 month after surgery. Results: Among 90 patients, 73.3% were male and 26.7% were female. Age 5 - 12 years is most commonly affected among all age groups, attributing to 58.9%, fall from height was the most common cause (58.9%) followed by road traffic accident (32.2%), fall of heavy object over head (7.8%) etc. The most common symptom was vomiting which was present in 85.6% of patients followed by altered consciousness in 72.2%, headache in 60% and scalp swelling in 25.6% of patients. The follow-up of our patients was 1 month after surgery. Most of our patients made good recovery. Among them 73 patients (81.1%) were neurologically intact (GOS 5), 10 (11.1%) patients had some deficit but could do their daily activity independently (GOS 4), 03 patients (3.3%) was dependant on other for daily activity with cognitive deficit (GOS 3) and 4 patients (4.4%) died. Conclusion:EDH in children can be managed by surgery with good outcomes. Even in the presence of poor initial clinical and radiologic conditions, timely intervention can lead to a good recovery. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 865-874